2014
DOI: 10.1038/jhg.2014.37
|View full text |Cite
|
Sign up to set email alerts
|

A labor- and cost-effective non-optical semiconductor (Ion Torrent) next-generation sequencing of the SLC12A3 and CLCNKA/B genes in Gitelman’s syndrome patients

Abstract: Gitelman's syndrome (GS) is a rare recessive disorder caused by mutations in the renal salt-handling genes SLC12A3 and CLCNKB. Our aim was to develop a next-generation sequencing (NGS) procedure for these genes based on two-tubes multiplex amplification of DNA pools and semiconductor sequencing with the Ion Torrent Personal Genome Machine (PGM). We created one pool with DNA from 20 GS patients previously Sanger sequenced for the coding exons of SLC12A3. A total of 13 mutations present in 11 of these patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…19 The NGS platform used in this study has great potential for clinical application. 2,20,28 Screening for rare variants of RNF213 should be considered for patients with MMD. In addition, categorization of the clinical phenotypes and advances in NGS tools will undoubtedly accelerate the identification of novel familial MMD and MMS variants and patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The NGS platform used in this study has great potential for clinical application. 2,20,28 Screening for rare variants of RNF213 should be considered for patients with MMD. In addition, categorization of the clinical phenotypes and advances in NGS tools will undoubtedly accelerate the identification of novel familial MMD and MMS variants and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA from the 255 patients was extracted from blood leukocytes using a QIAamp blood kit (Qiagen) and was sequenced with next-generation sequencing (NGS) using a custom-designed Ion AmpliSeq Panel (Life Technologies) and Ion Torrent personal genome machine (PGM). 28 As key words, "moyamoya disease" was searched in Online Mendelian Inheritance in Man (OMIN). RNF213 (moyamoya disease 2), ACTA2 (moyamoya disease 5), BRCC3 (moyamoya disease 4), and GUCY1A3 (moyamoya disease 6) had been reported as susceptibility or causative genes in MMD or MMS patients and were selected as target genes.…”
Section: Dna Sequencing and Data Analysismentioning
confidence: 99%
“…We had previously demonstrated that this pooling approach is valid to identify rare variants that are diluted by the common allele [11,12] . The DNA from each patient was obtained from blood leukocytes and adjusted to 10 ng/ μ L using the Real Time Taqman quantifi cation with RNase P (Life Technologies).…”
Section: Ngs Of Abcb1mentioning
confidence: 98%
“…The experimental procedure was reported elsewhere Tavira et al 2014), and full details are available upon request to the corresponding author. A twotube multiplex amplification for the coding sequence exons plus at least five intronic flanking nucleotides of NOTCH3 and HTRA1 was designated online (Ion AmpliSeq™ Designer v3.4; https://www.ampliseq.com).…”
Section: Next-generation Sequencingmentioning
confidence: 99%